(untitled) (International conference on multidisciplinary science, 2024)
Surgical correction of the coarctation of aorta is a vital procedure for treating aortic narrowing, a condition that can lead to restricted blood flow and various complications. Over the years, various surgical techniques have emerged, including end-to-end anastomosis, subclavian flap aortoplasty, patch aortoplasty, and extended end-to-end anastomosis, among others. These techniques have proven to be more effective and less invasive, minimizing the morbidity associated with traditional surgical methods.